2008
DOI: 10.1016/j.ijpara.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

African trypanosomiasis: Sensitive and rapid detection of the sub-genus Trypanozoon by loop-mediated isothermal amplification (LAMP) of parasite DNA

Abstract: Control of human African trypanosomiasis (HAT) is dependent on accurate diagnosis and treatment of infected patients. However, sensitivities of tests in routine use are unsatisfactory, due to the characteristically low parasitaemias in naturally infected individuals. We have identified a conserved sequence in the repetitive insertion mobile element (RIME) of the sub-genus Trypanozoon and used it to design primers for a highly specific loop-mediated isothermal amplification (LAMP) test. The test was used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
184
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(196 citation statements)
references
References 39 publications
7
184
2
2
Order By: Relevance
“…This technique has been proven to be an accurate, rapid and simple method, which amplifies the target nucleic acid under isothermal conditions (Notomi et al, 2000). Recently, wide applicability of LAMP in the detection of parasitic protozoa such as Babesia, Plasmodium, Leishmania and Trypanosoma in clinical samples has been demonstrated (Ikadai et al, 2004;Poon et al, 2006;Njiru et al, 2008;Takagi et al, 2009;Thekisoe et al, 2007;Laohasinnarong et al, 2011). Studies have also shown the application of LAMP to survey vectors of infectious diseases (Aonuma et al, 2009;Thekisoe et al, 2010;Nakao et al, 2010); however, these studies used purified DNA as a template for the LAMP assays.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been proven to be an accurate, rapid and simple method, which amplifies the target nucleic acid under isothermal conditions (Notomi et al, 2000). Recently, wide applicability of LAMP in the detection of parasitic protozoa such as Babesia, Plasmodium, Leishmania and Trypanosoma in clinical samples has been demonstrated (Ikadai et al, 2004;Poon et al, 2006;Njiru et al, 2008;Takagi et al, 2009;Thekisoe et al, 2007;Laohasinnarong et al, 2011). Studies have also shown the application of LAMP to survey vectors of infectious diseases (Aonuma et al, 2009;Thekisoe et al, 2010;Nakao et al, 2010); however, these studies used purified DNA as a template for the LAMP assays.…”
Section: Introductionmentioning
confidence: 99%
“…These tests amplify 18S ribosomal DNA or RNA, respectively, and as such cannot be used to distinguish between the two HAT types. Recently, loop-mediated isothermal amplification of DNA (LAMP) has been used for detection of members of the Trypanozoon subgenus as well as T. b. rhodesiense (11,12) subsequent to earlier studies targeting various trypanosomal genes (8,16). The reportedly high sen-sitivity, coupled with no need for specialized equipment, increases the likelihood of its adoption in resource-poor health centers where HAT is endemic.…”
mentioning
confidence: 99%
“…110 Present research eff orts focus on several areas: (i) recombinant or native trypanosome antigens that could be used to develop an improved serological test; (ii) methods to detect parasite antigens in blood or CSF; (iii) proteomic fi ngerprinting; (iv) low-tech PCR methods such as loop-mediated isothermal amplifi cation or oligochromatography; and (v) new blood or CSF markers of second-stage disease. [111][112][113][114][115] …”
Section: Diagnosismentioning
confidence: 99%